Conservative treatment in late term ovarian torsion: A Phase II experimental immunohistochemical study - Kazez, Ahmet; Akpolat, Nusret; Göksu, Mehmet (My University, 2010)
Aim: To investigate the ischemic changes in both ovaries by immunohistochemical method in the early and late postoperative periods after detorsion of the experimental delayed unilateral ovarian torsion. Material and Method: The study was performed in 4 groups with 6 Wistar-albino rats in each. group.Left ovary was considered as the study group. The other groups were as follows: Group (G) 1 (Control group): left ovarian fixation was performed initially and bilateral oopherectomy was applied after 48 hours. G2 (Torsion group): left ovarian torsion and fixation, followed by oopherectomy 48 hours later. G3 (Evaluation in the early period after detorsion): detorsion at 48 th hours following the torsion and bilateral oopherectomy after 48 hours of detorsion. G4 (Evaluation in the late period after detorsion): detorsion at 48th hours following the torsion and then bilateral oopherectomy performed after 21 days. Immunohistochemical staining was performed with double-blind technique using anti-Hsp-70 antibody to show the ischemic changes of the ovaries. Each positive staining was considered as one immunohistochemical staining score (IHSS). One-way ANOVA and post- hoc LSD tests were used for statistical analysis. Results: IHS scores indicated in parentheses were as follows: G1 (1), G2 (27), G3 (17) and G4 (19). Of the 27 IHSscores in G2, 23 points belonged to the study groups, while 4 points were related to contralateral ovaries. In G4, 11 points were calculated for contralateral and 8 points for the study group ovaries. There was statistically significant difference between Groups 2 and 4 with regard to IHS scores of the ovaries in the study groups (p<0.05). Discussion: Immunohistochemical methods have shown that viable ovarian tissue can be detected when detorsion was performed even after 48 hours of experimental ovarian torsion. Tissue injury due to ischemia significantly decreases ipsilaterally during the late postdetorsion period On the contrary, it was observed that tissue injury occurred at the contralateral ovary most probably as a consequence of ischemia/reperfusion. The results of the present study suggested that detorsion may be recommended for pediatric cases with delayed referrals after ovarian torsion.
Geç dönem over torsiyonlarinda konservatif tedavi: Ikinci basamak deneysel immunhistokimyasal çalisma
Keywords: Detorsion; Experimental; Immunohistochemistry; Management; Ovarian torsion